2006
DOI: 10.1007/s00232-006-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Basolateral Cl− Channels in Airway Epithelial Cells: The Role of Nitric Oxide

Abstract: The presence of basolateral Cl(-) channels in airway epithelium has been reported in several studies, but little is known about their role in the regulation of anion secretion. The purpose of this study was to characterize regulation of these channels by nitric oxide (NO) in Calu-3 cells. Transepithelial measurements revealed that NO donors activated a basolateral Cl(-) conductance sensitive to 4,4'-diisothiocyanatostilbene-2,2'-disulfonic acid (DIDS) and anthracene-9-carboxylic acid. Apical membrane permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…These experiments strongly suggest a direct association between bestrophin-3 expression and the cGMP-dependent I Cl(Ca) . The cGMP-dependence was previously also shown for human bestrophin-1 [184,196]. In contrast, the mouse bestrophin-3 variant expressed in the heart has no cGMP dependence [198].…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 72%
See 1 more Smart Citation
“…These experiments strongly suggest a direct association between bestrophin-3 expression and the cGMP-dependent I Cl(Ca) . The cGMP-dependence was previously also shown for human bestrophin-1 [184,196]. In contrast, the mouse bestrophin-3 variant expressed in the heart has no cGMP dependence [198].…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 72%
“…Several other groups have recently used siRNA technique in cell culture and found an association between the bestrophin proteins and I Cl(Ca) [179,181,185,195,196,197]. We have found that downregulation of bestrophin-3 in mesenteric small artery VSMCs with siRNA suppressed the cGMP-dependent I Cl(Ca) without affecting the co-expressed classical I Cl(Ca) [112].…”
Section: Bestrophins Are Strongly Associated With the Cgmp-dependent mentioning
confidence: 89%
“…Nitric oxide is generated from L-arginine by nitric oxide synthases and serves as a cell-signaling molecule in many physiologic processes (24). In the lungs, nitric oxide affects epithelial cell ciliary beat frequency (25) and transepithelial anion transport (26), which facilitate airway clearance. Nitric oxide affects parasympathetic nerve function, which controls bronchoconstriction (27).…”
Section: Discussionmentioning
confidence: 99%
“…Bestrophins (also known as BEST or VMD2) are members of a family of CaCC found in epithelial tissues that express Ca 2ϩ -activated Cl Ϫ currents (1)(2)(3). The recent discovery of the TMEM16 (also termed ANO) family of CaCC (4 -7) introduces additional questions regarding the molecular identity of the epithelial CaCC.…”
mentioning
confidence: 99%